Responsibility of States, Individuals and Legal Entities Towards Marine Pollution - Riry, Welly Angela; Waas, Armelia Febriyanti; Leatemia, Wilshen; Hattu, Vondaal Vidya; Noya, Ekberth Vallen (Fakultas Hukum Universitas Pattimura, 2025)
Introduction: Marine environmental pollution is a global concern today because it has an impact on environmental sustainability and the use of marine resources. This problem not only affects the national interests of coastal countries, but also has implications for the welfare of all mankind.Purposes of the Research: Examine and analyze regulations on the protection of the marine environment from pollution, as well as the responsibility of the state, legal entities, and even individuals for marine pollution.Methods of the Research: This research is a normative research using a legislative approach with the sources of legal materials used are primary, secondary and tertiary legal materials with qualitative analysis.Results of the Research: Pollution of the marine environment is a global challenge that requires international cooperation. UNCLOS 1982 has established rules regarding the responsibilities of states, legal entities, and individuals in efforts to prevent, reduce, and handle marine pollution. Along with the increasing exploitation of marine resources, both in the energy and transportation sectors, the risk of pollution, especially due to oil spills, is getting higher. Therefore, national regulations that are aligned with international standards are needed to ensure the sustainable protection of the marine environment as well as effective accountability and compensation mechanisms for affected parties.